A new species of Chimarra Stephens 1829 (Trichoptera: Philopotamidae) and new caddisfly records from Rio Grande do Norte State, Brazil - Queiroz, Larissa L.; Dias, Everton S.; Calor, Adolfo R. (Zootaxa, 2020)
Trichoptera is the largest order of exclusively aquatic insects, comprising more than 16,000 described species with cosmopolitan distribution. There are about 800 species recorded from Brazil so far, mostly from the North, Southeast, and South regions. In Northeastern Brazil, the state of Rio Grande do Norte has only one Trichoptera species recorded so far (Oecetis excisa). Here, Chimarra (Chimarra) potiguar n. sp. is described and illustrated. The new species can be easily distinguished from its congeners by the following features: Segment X has its mesal lobe elongate, sub-rectangular; lateral lobes long and rounded apically, dorsal margin with subapical invagination; the apex of each inferior appendage has a pronounced apicodorsal acute projection, and the phallotremal sclerite complex is curved, with small spines dorsally. Chimarra (C.) potiguar is morphologically similar to Chimarra (Chimarra) bidens, but the new species differs from it by the length and shape of the mesal lobe and lateral lobes of segment X, and by general shape of the basal regions of inferior appendages. Five additional caddisfly species are recorded for the first time from Rio Grande do Norte state: three in Hydropsychidae (Leptonema sparsum, Macrostemum hyalinum, and Smicridea (Smicridea) palifera) and two in Polycentropodidae (Cyrnellus fraternus and Cernotina bibrachiata).